ORGANIZATION OF INNOVATIVE PROCESSES IN GENERAL EDUCATION INSTITUTIONS - Jamshid Shamshidinovich Kazimov (Galaxy International Interdisciplinary Research Journal, 2023)
The article represents general secondary education, ensuring efficiency as an integral pedagogical system interconnected with innovative processes to increase the effectiveness of learning and learning processes in the organization and management of innovative processes